HUBUNGAN PENGETAHUAN DIABETES DENGAN KEPATUHAN PENGOBATAN PADA PASIEN DIABETES TIPE II DI RSPAD GATOT SOEBROTO - Raihan Akbar Darmawan (2023)
Diabetes mellitus is a chronic disease that requires a comprehensive patient management. Information and knowledge are two of the factors that facilitate medication adherence. The objective of this research was to find the relation between knowledge about diabetes and medication adherence degree of type II Diabetes Mellitus at RSPAD Gatot Soebroto, Central Jakarta. This research uses an analytic observational design with the cross-sectional method. The populations of this research are the DM type II outpatients who went to control at Gatot Soebroto Army Hospital on May 2023 with the total of samples are 64 people. The knowledge and the medication adherence degrees are measured with the Diabetes Knowledge Questionnaire (DKQ-24) and the Morisky-Green Levine Medication Adherence Scale (MGLS). 53.1% of the respondents have sufficient knowledge. 57.8% of the respondents have moderate adherence. From the result of Somer's d Gamma test, obtained p = 0.6 with the value -0.68. These show that p > 0.05 and can be interpreted as no significant relation between knowledge about diabetes and medication adherence degree of Diabetes Mellitus type II at RSPAD Gatot Soebroto